Banking Competition, Risk, and Regulation - Tieman, Alexander (IMF Working Papers; Working Paper ;, 2004)
In a dynamic theoretical framework, commercial banks compete for customers by setting acceptance criteria for granting loans, taking regulatory requirements into account. By easing its acceptance criteria a bank faces a trade-off between attracting more demand for loans, thus making higher per period profits, and a deterioration of the quality of its loan portfolio, thus tolerating a higher risk of failure. Our main results state that more stringent capital adequacy requirements lead banks to set stricter acceptance criteria, and that increased competition in the banking industry leads to riskier bank behavior. In an extension of our basic model, we show that it may be beneficial for a bank to hold more equity than prescribed by the regulator, even though holding equity is more expensive than attracting deposits.